Anodic Stripping Voltammetry of Arsenic Determination with Edible Mushroom-Nafion-Modified Glassy Carbon Electrode - Segura-Segura, R; Segura-Segura, R (Elsevier B.V., 2024)
An edible Mushroom-Nafion modified glassy carbon electrode (M2N5-GCE) was prepared using a homogeneous mixture varying the concentrations of these, in addition to the origin of the mushroom (Shiitake, Lentinula edodes, M1 and Abrantes, Agariscus bisporus, M2) and applied to the As(III) determination by anodic stripping voltammetry. After choosing the optimal conditions in the preparation of the electrode, the second stage was to study the effects of various parameters such as supporting electrolyte, pH, accumulation potential, and time (Eacc, tacc). The optimum experimental conditions chosen were Britton Robinson buffer 0.01 mol L−1 pH:4.6; Eacc: −1.0 and tacc: 60 s obtaining a signal of oxidation of As(0) to As(III) about 0.08 V. Peak current was proportional to arsenic concentration over the 19.6–117.6 μg L−1 range, with a 3σ detection limit of 13.4 μg L−1. The method was validated using As(III) spiked tap water from the laboratory with satisfactory results (RE:3.0 %). Finally, the method was applied to the determination of As(III) in water samples from the Loa River (Northern Chile) in the presence of As(V) in a concentration >20 times higher (RE: 2.3 %). © 2024